Qualitative experiences of new motorised mobility scooter users relevant to their scooter skills: a secondary analysis. (2nd January 2023) - Kirby, R. Lee; Smith, Cher; Mortenson, W. Ben; Battalova, Alfiya; Hurd, Laura; Hobson, Sandra; Jang, Sharon; Emery, Richelle
Abstract: Objective: To explore the experiences of new motorised mobility scooter users from the perspectives of the assessment and training of scooter skills. Design: Descriptive secondary analysis of qualitative data. Setting: Community. Participants: 20 New users of motorised mobility scooters. Interventions: Not applicable. Main outcome measures: Directed qualitative analysis of up to four semi-structured interviews over the course of the first year of scooter use, to identify themes and sub-themes that could inform recommendations regarding assessment and training protocols. Results: We identified two themes. The first related to potential new content . As one example of the sub-themes, there were many excerpts that dealt with the use of skills in various combinations and permutations that were used to carry out activities during everyday life and participate in society. These excerpts suggested the importance of training skills in combination to facilitate skill transfer (or generalizability). The second theme is related to enhancements of existing content . As one example of the sub-themes, there were several excerpts that dealt with scooter security. These excerpts led to the recommendation that removing and inserting the scooter key should be added to the assessment criteria for the "turns power on and off" skill of the Wheelchair Skills Test (WST) and its questionnaire version (WST-Q). Conclusions: The experiences of scooter users over the first year of receiving a scooter appear to be relevant to the assessment and training of scooter skills and suggest themes for further study. Clinical trial registration number: NCT02696213 IMPLICATIONS FOR REHABILITATION: The experiences of new scooter users are highly relevant to the assessment and training of scooter skills. These experiences suggest both potential new content and enhancements of existing content to the Wheelchair Skills Program Manual.